Трудно быть богом: Далекая радуга: повести / А. Н. Стругацкий, Б. Н. Стругацкий - Стругацкий Аркадий Натанович (Внеклассное чтение, 2006)
Экземпляры: (20080116) / Инвентарный номер: 43676 / Цена: / Сис.шифр: Р2 / Авт.знак: С 87 / ББК: 84(2Рос-Рус)-4